Data for: Fibroblast-driven collagen expansion and altered thymic medullary niches in 22q11.2 deletion syndrome - Ekwall, Olov (University of Gothenburg, 2026)
The aim of the study was to identify spatial transcriptomic and proteomic differences between thymic tissue from patients with 22q11.2 deletion syndrome and controls. Thymic tissue from two patients with 22q11DS and eight controls were subject to spatial transcriptomics and proteomics using Visium and Phenocycler methodologies, respectively.

The dataset contains data from the manuscript "Fibroblast-driven collagen expansion and altered thymic medullary niches in 22q11.2 deletion syndrome" by Hennings et al, which was submitted for publication in February 2026.

Syftet med studien var att identifiera skillnader avseende spatiala transkriptom och proteom mellan tymusvävnad från patienter med 22q11.2-deletionssyndrom och kontroller. Tymusvävnad från två patienter med 22q11DS och åtta kontroller analyserades med spatial transkriptomik och proteomik med hjälp av Visium- respektive Phenocycler-metodik.

Datasetet innehåller data från manuskriptet ”Fibroblast-driven collagen expansion and altered thymic medullary niches in 22q11.2 deletion syndrome” av Hennings et al., som skickades in för publicering i februari 2026.
Data för: Fibroblast-driven collagen expansion and altered thymic medullary niches in 22q11.2 deletion syndrome
Keywords: IMMUNE SYSTEM DISEASES; IMMUNSJUKDOMAR; Thymus Gland; Bräss; 22q11 Deletion Syndrome; 22q11-deletionssyndrom; Other diseases of thymus; Andra specificerade sjukdomar i tymus; Dysplasia of thymus gland with immunodeficiency; tymusdysplasi med immunbrist; Immunology in the Medical Area; Immunologi inom det medicinska området